Evaluating Healthcare Worker Performance through Leadership: A Malcolm Baldrige National Quality Award Approach at Benyamin Guluh Regional Hospital - Mustika Mustika; Sartini Risky; Andi Asri (Waluya The International Science of Health Journal, 2026)
Introduction: Benyamin Guluh Regional General Hospital in Kolaka Regency faces various challenges in healthcare service performance, including declining healthcare worker performance, leadership adaptability challenges, and weaknesses in strategic planning and performance measurement systems. This study aims to evaluate healthcare worker performance with a focus on the management dimension of leadership. Method: A qualitative research method with a case study design was applied, utilizing triangulation techniques from 12 informants, including the Director and Head of the Hospital Human Resources Department. Snowball sampling was used in selecting informants, with data analysis conducted inductively. Performance evaluation was based on the Malcolm Baldrige National Quality Award (MBNQA) Method. Result: The study results show that hospital leadership is effective but needs to improve adaptability in crisis situations. The existing strategic plan is clear but lacks flexibility and insufficient involvement of healthcare workers in planning. Customer focus is good, but capacity management needs improvement. The performance measurement system is effective but requires additional training. Conclusion: The need for adjustments in leadership and strategic planning to deal with crisis situations at the Benyamin Guluh Regional General Hospital, Kolaka Regency.